2020
DOI: 10.1111/jch.14013
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular death rates in a COVID‐19 low prevalence area

Abstract: The spread of COVID-19 pandemic was not homogeneous in Italy, with Northern regions bearing the greatest burden of the disease. In the Abruzzo region, in Central Italy, the province of L'Aquila is the closest to Rome, where the first two imported SARS-CoV-2positive cases have been detected as of January 29, 2020. With a population of 303 239 individuals and a total of 123 COVID-19 cases (40.6/100 000) as of March 31, 2020, the area was among the less affected in Italy (Figure S1, panel A). Specifically, no cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
0
17
0
3
Order By: Relevance
“…9,19 More recent evidences, consistent with our results, showed a significant decrease in mean number of endovascular therapies per hospital performed before and after COVID-19 confinement along with a significant increase in mean stroke onset-to groin puncture time 260 .A delayed presentation of STEMI patients that may led to worsened prognosis and unnecessary deaths has also been observed 261 . Moreover, an additional study confirmed that more in-hospital cardiovascular deaths occurred in March 2020 compared with March 2019, a finding possibly due to late hospital presentations and consequent greater disease severity that affected eligibility and outcome of cardiovascular procedures 262 .…”
Section: Discussionmentioning
confidence: 78%
“…9,19 More recent evidences, consistent with our results, showed a significant decrease in mean number of endovascular therapies per hospital performed before and after COVID-19 confinement along with a significant increase in mean stroke onset-to groin puncture time 260 .A delayed presentation of STEMI patients that may led to worsened prognosis and unnecessary deaths has also been observed 261 . Moreover, an additional study confirmed that more in-hospital cardiovascular deaths occurred in March 2020 compared with March 2019, a finding possibly due to late hospital presentations and consequent greater disease severity that affected eligibility and outcome of cardiovascular procedures 262 .…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, from March 10th to April 20th, 2020, the proportion of children and adolescents presenting to ophthalmological ED halved from 10 to 5.3% in comparison with 2019 [22]. Similarly, Del Pinto and colleagues reported a significant reduction in less all-cause and cardiovascular hospitalizations occurred from January 1st to March 31st, 2020, than in the similar period of 2019 in 5 Italian hospitals located in the province of L'Aquila (Southern Italy) [24]. These authors also reported a significant increase in intra-hospital deaths attributable to major cardiovascular diseases in March 2020 compared with the same month in 2019 (+ 6.8%), possibly due to barriers to seeking emergency care during COVID-19 pandemic [25].…”
Section: Discussionmentioning
confidence: 93%
“…6 Second, direct deaths from unfamiliar complications of Covid-19 such as coagulopathy, myocarditis, inflammatory processes, and arrhythmias may have caused confusion and led to attributions of death to other causes, especially early in the pandemic. [7][8][9] Third, Covid-19 death counts do not take into account the indirect consequences of the Covid-19 pandemic on mortality levels. [10][11][12] Indirect effects may include increases in mortality resulting from reductions in access to and use of health care services and psychosocial consequences of stay-at-home orders.…”
Section: Introductionmentioning
confidence: 99%
“…First, some direct deaths attributable to Covid-19 may be assigned to other causes of death due to an absence of widespread testing and low rates of diagnoses at the time of death [6]. Additionally, direct deaths from unfamiliar complications of Covid-19 such as coagulopathy, myocarditis, inflammatory processes, and arrhythmias may have caused confusion and led to attributions of death to other causes, especially early in the pandemic and among persons with comorbid conditions [79]. Second, Covid-19 death counts do not take into account the indirect consequences of the Covid-19 pandemic on mortality levels [10,11].…”
Section: Introductionmentioning
confidence: 99%